Effects of high temperature, high humidity, and cold storage on structure and qualities of whole oat flour noodles during processing. Issue 1 (12th December 2022) - Zhang, Yifu; Yang, Tongliang; Chen, Cheng; Wang, Jiake; Qiang, Siqi; Zhou, Junjun; Li, Shuhong; Chen, Ye
Abstract: Gelation and structure of oat starch significantly affect qualities of whole oat flour noodles. During extrusion, the structure of noodles is loose, resulting in high cooking loss and poor texture. Therefore, oat noodles were treated with high temperature, high humidity (HTH), and cold storage (CS), and their structure and qualities were analyzed. The results showed that compared with CS, HTH could reduce the cooking loss of noodles from 10.12% to 6.13%, increase the hardness (65.59 g) and chewiness (20.67) of noodles, and effectively improve the sensory quality of noodles. The change in texture and sensory of noodles was due to HTH by accelerating the retrogradation of starch in noodles, promoting the cross‐linking of starch molecules to form an ordered structure, causing an increase in the ordered degree and crystallinity of starch and making the structure of noodles denser. It made the mobility of water in the noodles decrease, and more tightly bound water was transformed into weakly bound water and free water. HTH can be applied to industrial production of whole oat flour noodles. This study could effectively guide the production of high‐quality whole oat flour noodles without any food additives.